Meta-analysis of Bonding Effectiveness to Zirconia Ceramics. (April 2014) - Inokoshi, M.; De Munck, J.; Minakuchi, S.; Van Meerbeek, B.
Dental zirconia can no longer be considered un-bondable to tooth tissue. In literature, an increasing number of papers indeed report on the bonding effectiveness of different luting techniques to zirconia. We aimed to disclose general trends in bonding to zirconia by systematically collecting zirconia bond-strength data. A search in PubMed and EMBASE revealed 1, 371 bond-strength tests reported on in 144 papers. A macro-shear bond-strength protocol was most frequently used; it revealed significantly lower bond strengths and was less discriminative than the other test methods. Regarding luting technique, the combination of mechanical and chemical pre-treatment appeared particularly crucial to obtain durable bonding to zirconia ceramics. The cement choice was not revealed as a determining factor after aging conditions, as long as composite cement was used. Regarding test protocol, a tensile test appeared more discriminative, particularly when combined with 'water storage' aging.